Determination of polybrominated diphenyl ethers in milk samples. Development of green extraction coupled techniques for sample preparation. Issue 3 (16th December 2016) - Berton, Paula; Mammana, Sabrina B.; Locatelli, Daniela A.; Lana, Nerina B.; Hapon, María B.; Camargo, Alejandra B.; Altamirano, Jorgelina C.
Abstract : Ultrasound‐assisted extraction (UAE), cloud point extraction (CPE), and ultrasound back‐extraction (UABE) techniques have been coupled for lixiviation, preconcentration, and cleanup of polybrominated diphenyl ethers (PBDEs) from milk samples for determination by gas chromatography‐electron capture detection (GC‐ECD). Physicochemical parameters that affect the efficiency of the extraction system were investigated using a design of experiments based on multivariate statistical tools, and considering the sample matrix along the development. The coupling of the leaching step, UAE, enhanced ca. 3.5 times the extraction efficiency of the former sample preparation methodology (CPE‐UABE) leading to cleaner sample extracts suitable for GC analysis. Under optimum conditions, the proposed methodology exhibits successful performance in terms of linearity and precision, with recoveries in the range of 68–70% and LODs within the range 0.05–0.5 ng/g dry weight (d.w.). The proposed sample preparation methodology coupled three green analytical techniques. It expands the application frontiers of CPE for the analysis of biological samples by GC. The optimized methodology was used for determination of PBDEs in powder milk samples, from both commercial and human sources.